(untitled) (Annals of Bangladesh Agriculture, 2021)
Application of phosphorus solubilizing microbes is a promising tool for enhancing P uptake in plant. The aim of this study was to evaluate the phosphate solubilization potential and growth promotion of pea (Pisum sativum L.) by native Trichoderma asperellum isolate G3. Phosphate solubilization by T. asperellum strain was assessed in National Botanical Research Institute’s Phosphate (NBRIP) broth medium. Pea plants were inoculated by Trichoderma strain and grown in pot in phosphate deficit condition. The fungal strain was able to solubilize phosphate (from 188.95±2.04 to 262.50±3.80 mgL-1) in broth at different time periods and decreased solution pH. The Trichoderma inoculated pea plant increased the root growth, shoot growth, leaf number, shoot biomass, root biomass, total dry weight, chlorophyll a, chlorophyll b and carotenoid by 23.9%, 33.3%, 33%, 37.1%, 32.7%, 28.4%, 24.5%, 17.4% and 14.7% respectively over control after 5 weeks of post inoculation. The results showed that the native T. asperellum isolate G3 has great potential in the phosphorus solubilization. Ann. Bangladesh Agric. (2020) 24(2) : 121-124